The Effect of Flavonoid Extract from Phaleria macrocarpa to Proliferating Factors (MMP-1, MMP-3, MMP-7) in Endometriosis Mice Model - Irwanto, Yahya; Wiyono , Teguh; Wardani, Kusuma (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Endometriosis is an inflammatory disease influenced by estrogen characterized by ectopic growth of the endometrial stroma and glands. Matrix metalloproteinase (MMP) is a proteolytic enzyme that has an important role in the remodeling of the extracellular matrix in normal tissues but also contributes to pathologies such as tumor invasion. The therapy has many drawbacks, including being expensive and in need of herbal therapy as an alternative. Phaleria macrocarpa is a native plant of Indonesia that contains flavonoids. This study aimed to evaluate the effect of Phaleria macrocarpa flavonoid isolate on the development of apoptosis, proliferation, and angiogenesis in mice model endometriosis. Material and Methods: This research is a true experimental study with a Randomized Post-Test Only with a Control Group in the laboratory. Samples are divided into six groups, a control group and an intervention group, administered with flavonoid extract from Phaleria macrocarpa. Data analysis was carried out by using the Independent T-Test with SPSS for Windows 19.0 software. Results: Each control and intervention group consisted of 6 mice. The normality test for each variable shows p> 0.05. Administration of flavonoid in each group shows a significant decrease in MMP-1 (20.4 ± 7.74 vs 65.68 ± 10.97, p=0.000), MMP-3 (53.34 ± 9.66 vs67.47 ± 10.05, p=0.000), and MMP-7 expression (40.52 ± 5.43 vs 54.13 ± 4.08, p=0.000). Conclusion: Flavonoids from the Phaleria macrocarpa fruit extract were able to reduce the expression of MMP-1, MMP-3, and MMP-7 in mice model endometriosis.